The Etheric Interpretation of Quantum Mechanics - Wang, Jian’an (European Journal of Applied Sciences, 2021)
In this paper, the physical explanation of all quantum phenomena such as wave function, wave function collapse, wave-particle duality, single-electron double-slit interference, uncertainty relation, tunneling effect and quantum entanglement is given by using the new etheric theory, and a new uncertainty relation which is consistent with the latest experimental results is given.